Copper‐Mediated Cyanation of Aryl Halides by Activation of Benzyl Cyanide as the Cyanide Source. Issue 19 (6th May 2013) - Wen, Qiaodong; Jin, Jisong; Mei, Yuncai; Lu, Ping; Wang, Yanguang
Abstract: Aryl nitriles were efficiently synthesized through copper‐mediated cyanation of aryl halides using benzyl cyanide as the cyanide source. Aryl halides with various substituents on the aromatic ring afforded the corresponding aryl nitriles in 32–97 % yields (25 examples). This reaction could also be carried on a gram scale by using commercially available reagents. Additionally, a C–H bond oxidation and a C–CN cleavage are proposed to be involved in this cascade process. Abstract : An efficient, copper‐mediated cascade synthesis of aryl nitriles from aryl halides using benzyl cyanide as the cyanide source is described. Compared with traditional copper‐mediated cyanation reactions, this approach effectively avoided the use of toxic MCN and low soluble reagents. Furthermore, C–H oxidation and C–CN cleavage are proposed to be involved in this cascade process.